Demographic and Histopathologic Profile of Pediatric Patients with Primary Brain Tumors Attending a Regional Cancer Center - Mehta, Dhruv Pankaj; Anand, Asha S; Patel, Dipak; Trivedi, Priti; Panchal, Harsha; Patel, Apurva; Shah, Sandip A (Indian Journal of Medical and Paediatric Oncology, 2019)
Background: Primary brain tumors (PBTs) are the most common solid childhood malignancies. However, epidemiologic profile of these tumors is scarce in developing nation like India. Objective of Study: The objective of this study was to study the demographic and histopathologic profile of pediatric patients with PBTs residing in Gujarat, and attending the Gujarat Cancer and Research Institute, Ahmedabad. Materials and Methods: Data regarding age, gender, anatomical site, and histopathology (according to the World Health Organization classification) of 242 patients with brain tumors (0–18 years) operated over 10 years (January 2006 to December 2015) were collected retrospectively, and analyzed. Results: Of total 242 patients with PBTs, 78.1% were from 5 to 14 years age group with the mean age being 9.38 ± 3.82 years (95% confidence interval). Brain tumors were more common in males (64.1%) as compared to females (35.9%) with a male-to-female ratio of 1.78:1. The most common anatomical site was cerebellum (46.3%), followed by cerebral hemispheres (14.1%). Infratentorial tumors (60.9%) were predominant than supratentorial tumors (39.1%) in 0–14 years age group while supratentorial tumors (58.3%) were predominant than infratentorial tumors (41.7%) in 15–18 years age group. Astrocytic tumors (38.9%) and embryonal tumors including medulloblastomas, supratentorial primitive neuroectodermal tumors, and atypical teratoid/rhabdoid teratomas (34.7%) were the most common histological subtypes comprising three-quarters of all tumors. Ependymomas (16.1%) and craniopharyngiomas (5%) were third and fourth most common tumors, respectively. Among astrocytic tumors, 71.3% were of lower grade histology (Grade I and II). Conclusions: Astrocytomas and medulloblastomas, which form the major histologic subtypes in children residing in Gujarat, needs special attention with respect to the distribution of infrastructure and resources. Histopathological profiles of cohort in this study do not differ substantially from other hospital-based and population-based studies.
Keywords: Astrocytoma; cerebellum; craniopharyngioma; ependymoma; medulloblastoma; supratentorial